Longitudinal-vertical dynamics of a high-speed train rescued by locomotives during braking on grades. Issue 6 (3rd June 2023) - Wei, Lai; Zeng, Jing; Qu, Sheng; Huang, Caihong; Wang, Qunsheng
Abstract : This paper describes the longitudinal-vertical coupling dynamics of a high-speed train rescued by locomotives during the braking process on grades. The coupler jackknifing behaviour under compressive forces will affect the running safety of the coupling train. In this paper, the longitudinal-vertical impacts by field testing for the locomotive to train rescue scenario are firstly introduced. The quasi-static force analyses of the train and couplers are carried out to study the coupler jackknifing mechanism on graded tracks. The three-dimensional dynamic model of the train and coupler system is then developed. In this model, the coupler rotational motions, hysteresis characteristic of draft gears, braking characteristic are taken into account. The typical responses during the braking process for the high-speed train rescued by the diesel locomotive are reproduced and verified. The running safety of the longitudinal-vertical interaction for selected scenarios is further evaluated. The Influences of train speed and track gradient on the longitudinal-vertical dynamics are also studied. Two improvement measures, including the limitation of the coupler pitch angle and coupler force, are discussed to provide possible solutions.